Spartan Constitution and Education - Бралић, Жељко (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract: Ancient Sparta is generally recognized as a Greek polis with specific and non-typical state system determined by firmly established set of laws, commonly considered (by Spartans and other Greeks of the time) as a constitution of lawgiver Lykourgos. Spartan constitution was the essence of the state, and this work reviews some of the main institutions established by the constitution. Principal section of the text is dedicated to the basic element and the major purpose of the state and the constitution itself – namely, to the spartan education. It is the peculiar Spartan education and training system called agōgē that particularly enabled ancient Spartans to maintain their durable military might and decisive influence in classical period. Lawgiver of Sparta dedicated primary function in the arrangement of the state itself to the educational system, principally focused on physical and moral education. Capital purpose of educational system was caracter forming of young Spartans who were expected, mainly on a battlefield in a hoplite phalanx formation, to materialize Spartan ideal of a paramount skilled combatant and fearless warrior.